2016
DOI: 10.3390/ijerph13080815
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Hospital Deliveries among Ethnic Minority Women with Religious Beliefs in China: A Descriptive Study Using Interviews and Survey Data

Abstract: Background: China has made great progress in improving hospital delivery-the coverage of hospital delivery has increased to above 95% in most regions- some regions lag behind owing to geographic and economic inequality, particularly the poor ethnic minority areas of the Sichuan Province. This study explores factors which may influence hospital delivery from multiple perspectives, with implications for practice and policy. Methods: A framework analysis approach was used to identify and categorize the main barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Comparing with the distribution of life-round women (≥15 years) and reproductive-aged women (15–49 years), the inequality of OB/GYN workforce distribution of women with maternal care requirements (per 1000 live births) was severer, this may require additional attention on the allocation of maternal professionals. Similar to the study of the inequality of paediatric workforce distribution in China [ 22 ], this study also highlighted very severe geographic distribution inequality, especially in the West region, this may not be a huge problem because the West region was less-populous when comparing with the other two regions, but this result still suggests that women in the West region may need to travel a longer distance to receive OB/GYN care services, and this may even cause bad consequences if the distance and transport become a major obstacle of care-seeking behaviours [ 32 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparing with the distribution of life-round women (≥15 years) and reproductive-aged women (15–49 years), the inequality of OB/GYN workforce distribution of women with maternal care requirements (per 1000 live births) was severer, this may require additional attention on the allocation of maternal professionals. Similar to the study of the inequality of paediatric workforce distribution in China [ 22 ], this study also highlighted very severe geographic distribution inequality, especially in the West region, this may not be a huge problem because the West region was less-populous when comparing with the other two regions, but this result still suggests that women in the West region may need to travel a longer distance to receive OB/GYN care services, and this may even cause bad consequences if the distance and transport become a major obstacle of care-seeking behaviours [ 32 ].…”
Section: Discussionmentioning
confidence: 97%
“…The levels of inequality varied among different sub-groups of OB/GYN workforce, regarding the demographic distribution (except live births), the level of inequality of midwives was the highest, this may reflect the shortage of midwives, especially in the East region, however, regarding the distribution of live births, the inequality was the highest in the West region, more attention should be given in this maldistribution of midwives because skilled birth attendance is essential for safe delivery, maternal and newborn lives [ 32 , 33 ]. However, the comparison of inequality of OB/GYN doctors and OB/GYN nurses was not the in line with the results of paediatricians and paediatric nurses, in this study, the OB/GYN doctor distribution was found to be more inequitable than OB/GYN nurse distribution, this may indicate that the OB/GYN doctors were in shortage than OB/GYN nurses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of consumers are still concerned about freshness and food waste ( Yu et al, 2020 ). Unlike in a brick-and-mortar store where shoppers can visibly check the freshness of their produce, this is more difficult with home delivery ( Song et al, 2016 ). Thus, brands must try and opt for packaging that can keep food safe and fresh during transit and displays its freshness to re-assure customers.…”
Section: Background Descriptionsmentioning
confidence: 99%
“…The proportion of women whose highest educational level was elementary school or below in the 4 western provincial regions of Tibet, Xinjiang, Qinghai, and Yunnan was 83.5%, 37.1%, 52.9%, and 53.9%, respectively, which is higher than that of other provincial regions (http:// www.stats.gov.cn/tjsj/ndsj/2014/indexch.htm). Influenced by traditional customs, women in these areas, where the proportion of the ethnic minority or indigenous population is high, prefer to give birth at home [27][28][29][30]. Low levels of education or even illiteracy may limit the ability or willingness of women to seek the provision of formal healthcare services [31].…”
Section: Plos Medicinementioning
confidence: 99%